Placental Growth Factor (PlGF) in Women with Suspected Pre-Eclampsia Prior to 35 Weeks' Gestation: A Budget Impact Analysis. - Suzy Duckworth; Lucy C Chappell; Paul T Seed; Lucy Mackillop; Andrew H Shennan; Rachael Hunter (PLoS ONE)
Objective To model the resource implications of placental growth factor (PlGF) testing in women with suspected pre-eclampsia prior to 35 weeks' gestation as part of a management algorithm, compared with current practice. Methods Data on resource use from 132 women with suspected pre-eclampsia prior to 35 weeks' gestation, enrolled in a prospective observational cohort study evaluating PlGF measurement within antenatal assessment units within two UK consultant-led maternity units was extracted by case note review. A decision analytic model was developed using these data to establish the budget impact of managing women with suspected pre-eclampsia for two weeks from the date of PlGF testing, using a clinical management algorithm and reference cost tariffs. The main outcome measures of resource use (numbers of outpatient appointments, ultrasound investigations and hospital admissions) were correlated to final diagnosis and used to calculate comparative management regimes. Results The mean cost saving associated with the PlGF test (in the PlGF plus management arm) was £35,087 (95% CI -£33,181 to -£36,992) per 1,000 women. This equated to a saving of £582 (95% CI -552 to -£613) per woman tested. In 94% of iterations, PlGF testing was associated with cost saving compared to current practice. Conclusions This analysis suggests PlGF used as part of a clinical management algorithm in women presenting with suspected pre-eclampsia prior to 35 weeks' gestation could provide cost savings by reducing unnecessary resource use. Introduction of PlGF testing could be used to direct appropriate resource allocation and overall would be cost saving.